ANALISIS POTENSI PENERIMAAN KUALITAS ALUMNI PROGRAM STUDI EKONOMI SYARI’AH STAIN KUDUS DITINJAU DARI PERSPEKTIF STAKEHOLDER - Ningsih, Ekawati Rahayu (LP2M IAIN kUDUS, 2015)
GRADUATES RECEPTION QUALITYANALYSIS OF THE POTENTIAL ECONOMIC STUDIES SYARI’AH IN STAIN KUDUS VIEWED FROM THE PERSPECTIVE STAKEHOLDER. The first aim of this study was to determine the potential reception of graduates quality in Shariah Economic Studiesof STAINKudus in the world of work. Second, to determine the motivations and needs of stakeholders on the acceptance of the quality of graduates in Economics Shariah STAIN Kudus.And third, to determine what factors which are supporting and inhibiting the absorption of graduates of the Department of Shariah Economics STAIN Kudus in working world. The theory that was developed as a basis for the analysis is the pyramid theory of motivation and needs of Abraham Maslow. By using qualitative research approach, the analysis and discussion of this study are:First, the potential acceptance of Shariah Economy graduates in the working world, especially in the banking and financial institutions Shari’ah is still very large and potentially growing along with the rapid growth in the number of banking and financial institutions Shari’ah in Indonesia. Second, motivation and needs of stakeholders for the graduates reception of Shariah Economic STAIN Kudus is because it is the only college in the state of religion around the Pantura area having Shariah Economic Studies Program and easily accessible. In addition, in order to establish a more synergistic relationship with the STAIN kudus then either the shari’a banking and financial institutions are willing to accept graduates of Shariah Economic Studies Program as employees, of course, with the various criteria established in the job requirements.Keywords:Potential, Quality Admissions, Graduates, Economic Shariah, Stakeholder.Tujuan penelitian ini adalah: Pertama, untuk mengetahui potensi penerimaan kualitas alumni Program Studi Ekonomi Syari’ah STAIN Kudus di dunia kerja. Kedua, untuk mengetahui motivasi dan kebutuhan stakeholder terhadap penerimaan kualitas alumni. Dan ketiga, untuk mengetahui faktor-faktor apa saja yang menjadi pendukung dan penghambat penyerapan alumni Ekonomi Syari’ah Jurusan Syari’ah STAIN Kudus di dunia kerja. Teori yang dikembangkan sebagai dasar analisis adalah teori piramida motivasi dan kebutuhan dari Abraham Maslow. Dengan menggunakan pendekatan penelitian kualitatif, hasil analisis dan pembahasan dari penelitian ini adalah:Pertama, potensi penerimaan lulusan Ekonomi Syari’ah di dunia kerja, terutama di lingkungan perbankan syari’ah dan lembaga keuangan syari’ah masih sangat besar dan potensial seiring dengan semakin berkembang pesatnya pertumbuhan jumlah perbankan syari’ah dan lembaga keuangan syari’ah di Indonesia. Kedua, motivasi dan kebutuhan stakeholder terhadap penerimaan alumni Ekonomi Syari’ah STAIN Kudus adalah karena STAIN Kudus merupakan satu-satunya perguruan tinggi agama negeri di sekitar wilayah Pantura yang memiliki Program Studi Ekonomi Syari’ah dan mudah diakses. Selain itu, untuk menjalin hubungan yang lebih bersifat sinergis dengan STAIN Kudus, maka baik perbankan syari’ah maupun lembaga keuangan syari’ah bersedia menerima alumni Program Studi Ekonomi Syari’ah sebagai karyawan, tentunya dengan berbagai kriteria yang telah ditetapkan dalam persyaratan kerja. Kata Kunci: Potensi, Penerimaan Kualitas, Alumni, Ekonomi Syari’ah, Stakeholder.